Intake of trans fatty acids and low-density lipoprotein size in a Costa Rican population - Kyung Kim, Mi (2003)
Intervention studies show that dietary composition altered low-density lipoprotein (LDL) particle size, but population studies are scarce, and the potential effects of trans fatty acids (FA) on LDL size are unknown. Trans FA intake has been associated with a more atherogenic lipid profile and increased coronary heart disease (CHD). We examined the association between dietary intake, including trans FA and LDL size, in 414 randomly selected subjects living in Puriscal, Costa Rica. Dietary intake was assessed by a validated food frequency questionnaire (FFQ). Women had larger LDL size (Å) compared with men (263 v 261), and large LDL particles were correlated with increased intake (% energy) of protein (P = .005), animal fat (P = .041), trans FA (P < .0001), and decreased intake of carbohydrate (P = .052) in sex-, age-, and total energy intake-adjusted models. The correlation between trans FA intake and large LDL was significant in multivariate models that included dietary and nondietary factors; a 1% difference in trans FA was associated with a 2.44 Å increase in LDL size (P = .004). In sum, it is possible that the effects of dietary factors, such as intake of trans FA on CHD are mediated through their effects on LDL size.